MANAJEMEN PENDIDIKAN PESANTREN : STUDI KASUS DI PONDOK PESANTREN NURUL ISLAM NGABANG - Irawan, Deni; Aunurrahman, Aunurrahman; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aim to describe the management of Islamic boarding schools conducted by the Nurul Islam Ngabang Islamic Boarding School. The management described is namely: planning, organizing, implementing, and supervising the management of Islamic boarding school education. The approach used in this study was a qualitative approach with case study design. Data collection techniques are: interviews, direct observation, and documentation. For data analysis using descriptive techniques. Planning management of pesantren education, the foundation carries out: Planning about the objectives of the pesantren, Planning the formulation of the pesantren's vision and mission, Planning the curriculum used, Planning the procurement of facilities and infrastructure, Planning on financing. Organizing management by: Socializing tasks and educator functions in carrying out teaching tasks, Selection of pesantren education and teaching staff, Recruitment of students, Management of facilities and infrastructure. The implementation carried out are: building a measurable meeting agenda as a means of communication that is built between administrators, caregivers, students and parents of students, carrying out dormitory programs, implementing formal education and boarding programs. And supervision is carried out: supervision of achievement of goals, supervision of tasks of education and education personnel, supervision of curriculum achievement, supervision of funding, and supervision of facilities and infrastructure.Â Keywords: Education Management, Islamic Boarding SchoolsÂ